Outcome of Severe Pneumonia in Pediatric Patients Aged 2 Months to 5 Years - Yasmeen, Uzma; Liaqat, Samra; Qureshi, Aamer Naseer; Farooqi, M. Irfan; Zafar, Sadia; Aamer, Fauzia (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of outcome of severe pneumonia in children having age from 2 months to 5 years. Study Type: Descriptive Cross sectional study. Setting: Department of Pediatrics, Allied Hospital, Faisalabad. Duration: 14 March 2025 - 14 June 2025. Methodology: Total 190 patients with severe pneumonia of age 2 months to 5 years were included. Children with congenital lung pathologies like cystic fibrosis, immunodeficiency, recurrent chest infections in cerebral palsy patients, penetrating lung injuries with pneumonia, congenital heart disease, reactive airway disease, asthma, and bronchiolitis, as well as malnutrition were excluded. All patients received the WHO's recommended treatment regimen for treating pneumonia. IV antibiotics i.e cefzone and penicillin were injected after proper dose calculation. Patient’s oxygen saturation and respiratory rate were monitored hourly by a staff nurse.  Report of arterial blood sample sent to the laboratory as well as adverse outcomes including prolonged hospital stay, need for mechanical ventilation and moratlity were recorded. Results: The mean age was 3.82+1.17 years.  According to the gender distribution, 98 cases (51.58%) were male and 92 cases (48.42%) were female. According to descriptive duration of illness, 124 (65.26%) were ≤3 days and 66 (34.74%) were >3 days. Mean duration of illness was 4.24 ± 2.87 days.  According to vaccination status descriptive statistics, there were 86 unvaccinated cases (45.26%) and 104 vaccinated cases (54.74%). The mean hospital stay was 10.04 + 6.26 days. Prolonged hospital stay, need for mechanical ventilation and mortality were noted in 77.53%, 33.18% and 9.47% respectively. Conclusion: Pneumonia specially under five years of age is a major cause of morbidity and mortality.